THE ABILITY IN USING IDIOMATIC EXPRESSIONS BY ENGLISH DEPARTMENT STUDENTS OF NUSA CENDANA UNIVERSITY - Seran, Yanuarius (British (Jurnal Bahasa dan Sastra Inggris), 2021)
AbstractThe objectives of this research were to know how far the sixth-semester students specifically class A of English Study Programme of Nusa Cendana University comprehended idiomatic expressions, and what appeared to be the issues in comprehending it. A descriptive method was utilised to analyse the data. While in collecting the data, a set of tests and questionnaires dealing with idiomatic expression were given to 28 students, since the total number of class A of the sixth-semester students was 28. The students were asked to do the test which was classified into three parts, namely, multiple-choice test, completion test, and true-false test. The result showed that the students’ comprehension of idiomatic expression was 43.21% which was classified as at a fair level. There were some factors contributing to this condition. (1) The students tended to interpret the idiomatic expression literally. (2) lack of knowledge about the culture’s background of the target language that is being learned. This is because idiomatic expression cannot be interpreted literally but it should be interpreted contextually and culturally. Then, the problems were faced by the students were lack of vocabulary, and unfamiliar texts that contained idiomatic expression which were still new for the students.  Keywords: Ability, Idiomatic Expression, Problems